Peran Teknologi dalam Pembelajaran Bahasa untuk Meningkatkan Efektivitas dan Relevansi Pendidikan Masa Depan - Aliyah Suci Pradani NR; Usman, Sopianti; Dwinda Putri Aminuddin, Nasywa; Candra Dewi, Anita (AIJER: Algazali International Journal Of Educational Research, 2025)
Abstract: The development of digital technology has significantly influenced the way we learn, including in the realm of language learning. This transformation requires the integration of digital literacy skills and language proficiency. This study was conducted to explore the role of technology in language learning in the digital age, to evaluate how effectively technology enhances the quality of learning, and to provide strategic recommendations for the sustainable use of technology in language education. The research employed a descriptive qualitative approach through a literature review. Data were collected from various relevant academic sources. The findings reveal that the use of technology, such as e-learning applications, social media, and digital communication platforms, can improve learning productivity, enhance the effectiveness of the learning process, and broaden access to learning resources. However, without proper regulation, the use of technology may also lead to issues such as decreased concentration and student dependency. Therefore, it is essential to develop well-planned strategies for technology use that focus on character development. In conclusion, technology plays a significant role in enhancing the quality of language learning, as long as it is used wisely and purposefully